The Effect of Problem Based Learning Models on Interpersonal Intelligence and Student Learning Outcomes in Science Subjects - Farha Nazilah; Mayarni Mayarni (Postgraduate, University of Mataram, 2023)
Interpersonal intelligence is important for achieving learning goals and learning outcomes are the output of the teaching and learning process. This research aimed to examine the impact of the problem-based learning paradigm on students' achievement in science classes and their development of social skills. The participants in this study were fifth graders. 45 pupils were selected at random using a cluster sampling technique methods of information collection that make use of examinations and polls. Quantitative descriptions were used in the data analyses. The significance value (2-tailed) for the study's findings regarding interpersonal IQ, based on the independent sample t-test, was 0.005 < 0.05. The (2-tailed) significance level of the learning outcomes is 0.000 < 0.05. This shows that Ho is refuted and Ha is accepted in terms of the criteria used to make judgments while testing a hypothesis. In order to increase interpersonal intelligence and student learning outcomes, problem-based learning approaches are used.